Curiosity Cartography: Way Finding System Design - Miao, Yang (Transactions on Economics, Business and Management Research, 2024)
This paper analyzes the background concept of Hong Kong M+ Museum, extracts the word "connection" as the main concept of the new way finding system, analyzes the shortcomings of the current way finding system, optimizes and innovates the current way finding system, and adds a Child-friendly design to prevent children from getting lost. Strengthen the location of the service desk and the easy-to-remember areas in the museum to help visitors establish a sense of space.